(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopamine-producing neurons in the substantia nigra, affecting movement and cognition. While genetics and aging play roles in its onset, environmental toxins like paraquat—a widely used herbicide—are increasingly linked to PD due to their ability to generate reactive oxygen species (ROS) and induce oxidative stress. This study explores the neuroprotective potential of L-citrulline against paraquat-induced Parkinsonism. Fifteen adults male Wistar rats were divided into three groups: a control group receiving distilled water, a paraquat-only group (15 mg/kg), and a group receiving both paraquat and L-citrulline (200 mg/kg). Treatments were administered orally on alternate days for 21 days. Behavioral and biochemical tests assessed memory performance and oxidative stress. Rats treated with both paraquat and L-citrulline showed improvements in cognitive function and reduced oxidative damage compared to those given paraquat alone. Notably, L-citrulline lowered lipid peroxidation levels and enhanced memory-related task performance. These findings suggest that L-citrulline may mitigate paraquat-induced neurotoxicity by restoring redox balance and preserving neuronal health, highlighting its potential as a therapeutic agent for PD-like symptoms driven by oxidative stress.